OFR-85-78 A Study Of Conveyor Belt Training - Mechanics And Controls - George Saliba (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report disucsses the formulation of a mathematical model for the steering of a conveyor belt by a flat return idler and a troughed idler under various loading conditions. Significant parameters associated with belt training are identified. The generation of a skewed flat return idler model in terms of a steering force and self-aligning torque is presented. Development of the mathematical model for the flat return steering idler is illustrated for the case of no circumferential slip occurring and for the assumption of a bidirectional slip mechanism. Experimental results supporting the theoretical analysis is presented.